Health Risks Assessment of Heavy Metal from Consumption of Oreochromis Mossambicus and Oreochromis Niloticus in Denpasar, Bali - Ni Made Utami Dwipayanti; I Gst. Ayu Kunti Sri Panca Dewi; Ni Putu Gita Saraswati Palgunadi; Muliana Rofida; Ni Ketut Sutiari; I Gede Herry Purnama (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: Heavy metals in the environment can accumulate in organisms through the food chain process. Previous studies recorded heavy metal concentrations above threshold limits value in Badung river, which warrants monitoring adverse health outcomes due to consuming fish from this river. This research aimed to estimate the potential risk from heavy metals exposure, namely Pb, Cd, Cu, and Cr, due to fish consumption. Methods: Fish samples were limited to Oreochromis Mossambicus and Oreochromis niloticus, commonly known as tilapia. Twenty samples of composite fish muscles were collected from three fishing sites. Subsequently, the heavy metals present in the samples were quantified using an atomic absorption spectrophotometer (AAS), and health risks were assessed by calculating estimated daily intake (EDI) and target hazard quotient (THQ) for both carcinogenic and non-carcinogenic risks. Results and Discussion: The average concentrations of Pb in Oreochromis Mossambicus (6.35±3.21 mg/kg) and Oreochromis niloticus (6.09±3.07 mg/kg) exceed the threshold limits value for fish products, but other heavy metals remain below. The average EDI from consuming Oreochromis Mossambicus with Pb is 0.0025-0.0026 mg/kg/days; Cu is 0.0037- 0.0062 mg/kg/day; Cr is 0.0001 mg/kg/day. EDI from consuming Oreochromis niloticus with Pb is 0.0015-0.0025 mg/kg/day; and 0.00 mg/kg/day for Cu and Cr. The THQ calculation for carcinogenic and non-carcinogenic health risks showed no health risk from consuming the fish from the Badung River. Conclusion: The study concludes that the consumption of Oreochromis Mossambicus and Oreochromis niloticus from the Badung River was generally safe from potential health risks.